Teacher Readiness in Implementing the Merdeka Curriculum in Kerinci Regency - M. Nurzen (research, training and philanthropy institution Natural Aceh, 2022)
Merdeka Curriculum is a curriculum issued by the Indonesian Ministry of Education and Culture in 2020 as an effort to strengthen the nation's character and adapt to the times. The implementation of this curriculum requires readiness from various parties, including teachers as direct implementers in schools. This research aims to find out the teacher's mental readiness and knowledge readiness about the independent curriculum. This research uses a descriptive qualitative approach. The data sources in this study are teachers who teach at SD Negeri Sekolah Penggerak in Kerinci Regency. This research data collection technique is using interview and documentation techniques. The data analysis technique of this research is by doing data reduction, data presentation, and verification/conclusion. The results of this study show (1) Mentally to face challenges and changes in implementing the Merdeka Curriculum, teachers have confidence and enthusiasm. (2) The teacher's ability to implement the Merdeka Curriculum, the teacher has a fairly good ability seen in how the teacher compiles teaching modules with minor adjustments based on the sample modules provided by the Ministry of Education and Culture, prepares teaching materials and evaluations by adjusting the characteristics of students. The conclusion of this study shows that teacher readiness in implementing the Merdeka Curriculum is categorised as quite ready